A Distinct Clinical Entity of Invasive Cardiac Aspergillosis: Not the Heart Valves This Time - Zaid Al Khouri; Hunter Smeltzer; Anood Al Qura’an; Mohammad H. Khan; Alexandre E. Malek (Journal of Fungi)
Invasive aspergillosis (IA) is a life-threatening infection that mainly affects immunocompromised hosts. Cardiac involvement is rare but can be the sole presentation of IA. It is associated with a high mortality rate and mostly occurs in patients with pre-existing cardiac disease. It can also be seen in immunocompetent patients with a structurally normal heart. The reported cases of cardiac involvement are usually due to infectious endocarditis (IE) caused by Aspergillus species (most commonly Aspergillus fumigatus). However, there is limited data on non-valvular cardiac aspergillosis (NVCA). We reviewed 67 cases of NVCA published between 1950–2024 and reported an additional case from our institution involving a 48-year-old female with kyphoscoliosis diagnosed with Aspergillus pericarditis.